2023
DOI: 10.3389/fimmu.2023.1087345
|View full text |Cite
|
Sign up to set email alerts
|

Association of systemic immune inflammatory index with all-cause and cause-specific mortality in hypertensive individuals: Results from NHANES

Abstract: BackgroundThe relationship between the systemic immune inflammatory index (SII) and the prognosis of hypertensive patients is unclear. This study aims to explore the association of SII with all-cause and cause-specific mortality in patients with hypertension.MethodsThis study included 8524 adults with hypertension from the National Health and Nutritional Examination Surveys (NHANES) 2011–2018, and followed for survival through December 31, 2019. Cox proportional hazards models were used to investigate the asso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
14
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(35 citation statements)
references
References 48 publications
3
14
0
Order By: Relevance
“…The associations of SII with cancer and all-cause mortality showed the same trend. The same phenomenon was observed in a previous study of SII in hypertensive patients in the NHANES database in relation to all-cause mortality and cancer mortality (25), suggesting that low levels of immune in ammation in the body is another risk factor for…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…The associations of SII with cancer and all-cause mortality showed the same trend. The same phenomenon was observed in a previous study of SII in hypertensive patients in the NHANES database in relation to all-cause mortality and cancer mortality (25), suggesting that low levels of immune in ammation in the body is another risk factor for…”
Section: Discussionsupporting
confidence: 86%
“…Interestingly, the analysis showed that there was a little change of cardiovascular mortality with SII in cancer patients before the threshold (p 0.05), after which high SII levels were associated with high mortality. This has been reported for the rst time in cancer patients, but there are similarities to studies in other populations (25)(26)(27).…”
Section: Discussionsupporting
confidence: 83%
“…As clearly shown in Figure 6, the risk of LEDVT first decreased and then increased rapidly with the rise of ln(SII). Although no previous study has investigated the dose-response relationship, similar non-linear associations were found between SII and risk of all-cause mortality (35,36), arrhythmias (37), and rheumatoid arthritis (38). In these studies, the threshold values of ln(SII) were 5.97 × 10 9 /L (35), 6.57 × 10 9 /L (36), and 6.36 × 10 9 /L (38), respectively.…”
Section: Discussionmentioning
confidence: 55%
“…The possible pathways include oxidative stress and immune-inflammation. 8,16,17 Numerous epidemiolog-ical studies have found that higher levels of heavy metals, including Pb and Cd, are associated with increased levels of systemic inflammatory biomarkers such as C-reactive protein (CRP), white blood cells, and eosinophils. 18,19 Heavy metals are considered environmental endocrine disruptors, which elevate systemic inflammation and promote metabolic disease.…”
Section: Introductionmentioning
confidence: 99%
“…However, the mechanisms underlying these consistent associations remain unclear. The possible pathways include oxidative stress and immune‐inflammation 8,16,17 . Numerous epidemiological studies have found that higher levels of heavy metals, including Pb and Cd, are associated with increased levels of systemic inflammatory biomarkers such as C‐reactive protein (CRP), white blood cells, and eosinophils 18,19 .…”
Section: Introductionmentioning
confidence: 99%